Consecutive Jailed- and Kissing-Corsair Technique: Side Branch Protection and Dilation during Stent Implantation - Choi, Jungho; Kim, Byeong-Keuk; Hong, Sung-Jin; Hong, Myeong-Ki; Jang, Yangsoo (Yonsei medical journal, 2019)
The primary concern in percutaneous coronary intervention for bifurcation lesions is occlusion of a side branch after stenting of a main branch, especially in high-risk patients. We describe a novel technique, consecutive jailed- and kissing-Corsair technique, using a Corsair microcatheter for protection of side branches in bifurcation lesions.